The effects of political competition on rural land: Evidence from Pakistan - Kosec, Katrina; Haider, Hamza S.; Spielman, David J.; Zaidi, Fatima (International Food Policy Research Institute, 2015)
Can more vigorous political competition significantly raise rural land values, or contribute to more robust land rental markets? Exploiting exogenous variation in the national popularity of Pakistan’s political parties during the 2008 elections, we show that provincial assembly constituencies with greater competition between political parties had significantly higher land values and more active land rental markets four years later. A standard deviation decrease in a Herfindahl–Hirschman Index (HHI) of political concentration is associated with a 36 percent increase in land values, an 8 percentage point increase in the share of landowners renting out land, and an additional 4 percentage points of each landowner’s land being rented out. Land values appear to increase most among the poorest households, suggesting that benefits are greatest for those with the fewest resources to influence policy. Exploring potential causal mechanisms, we show that political competition leads to more stable and businessfriendly governance and institutions, better amenities, and greater provision of publicly provided goods. The effect of political competition on security is ambiguous, suggesting that political competition may decrease security along some dimensions and increase it along others.